PROFITABILITY OF DUCK ENTERPRISES IN OYO AND LAGOS STATES, NIGERIA - Baruwa, O. I.; Tijani, A. A.; Alimi, T. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2018)
The prevailing malnutrition problem in Nigeria is attributed to low animal protein intake. A panacea for this protein deficiency problem is to embark on accelerated protein production from poultry species with high growth rate in meat production, quick income generation and high profit.  One of such potential source of animal protein, which is not popularly produced in Nigeria, is duck. The objective of the study is to determine the costs and returns to duck enterprises in an attempt to examine the profitability of duck enterprises in Oyo and Lagos States in South-western Nigeria. A multistage sampling technique was used to select two hundred respondents. Data on quantities and prices of inputs and outputs were collected from the respondents. Data were analysed using enterprise budgeting. Results of the analyses indicated that the duck farmer who was in duck eggs enterprise has estimated higher profit margin (82.1), return per naira outlay (4.8), benefit cost ratio (5.6) than his counterparts in broiler and duckling enterprises. Farmers who were in duck egg enterprise has higher earnings per N1 expended on labour (38.8) compared to his counterparts in broiler and duckling enterprises. However, duck enterprises were profitable but the profit (N 301, 814.8) accruable to an average farmer from duck egg enterprise was higher than those obtained from broiler (N 41, 486.4) and duckling (N1, 403) enterprises. It is therefore recommended that livestock extension officers should educate the poultry farmers to embrace commercial production of duck enterprises.